The effect of foreign films and series on the behavior of some young people (Journal of the College of Basic Education, 2023)
One of the most important features of our world today is the rapid scientific and technological development, especially inThe field of communication and its advanced and different modern means, and from its results it became possible for the recipientIn any part of the world, he can watch and hear events when they happen in any part of the world.our world.(Recent years have witnessed a marked increase in the severity of cross-border problems.such as drug problems, money laundering crimes, illegal immigration, extremism and terrorismenvironmental pollution and deadly diseases). 7- (pg.) 195These large rapid steps in development brought about wide and important changes in the behavior of thecustoms and traditions of the recipient, even in other cultural, social, economic and political aspects.Even the psychological ones, the research and studies that dealt with the means of mass communication, in particularThe means of communication (television) has proven to have the ability to have a clear and direct impact on the thoughts ofattitudes and behavior of the recipient, and this influence, with its positive and negative implications for concepts and values.customs, trends, traditions, various considerations of life, and what he needs to acquireSkills and experience in developing human and spiritual concepts and values that have a direct impactin his behaviour, attitudes and beliefs.